2022
DOI: 10.1002/ldr.4217
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of soil aggregate‐related C‐N‐P stoichiometric characteristics with stand age and soil depth in Chinese fir plantations

Abstract: Soil C‐N‐P stoichiometry offers an effective way to explore the balance, limitation, cycling, and distribution of chemical elements in Chinese fir plantations. This research aimed to explore how soil organic C (Corg), total N (Ntot), and total P (Ptot) contents and stocks, together with their stoichiometric ratios vary with stand age (3, 9, 17, and 26 years) as well as soil layer (0–10, 10–20, 20–30, and 30–40 cm) at aggregate scales in Chinese fir plantations from Guangxi, China. For Chinese fir plantations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 62 publications
2
21
0
Order By: Relevance
“…Regardless of the stand type, there were significant differences in OC and TN contents associated with different aggregate sizes, which is shown in Table 2. In this research, OC and TN contents were mainly concentrated in microaggregates (Figure 3), conforming to the results by Mao et al (2021) and Tang and Wang (2022) that microaggregates have larger specific surface areas, causing the adsorption to nutrients to improve. Similarly, our findings detected that soil OC and TN contents with sized aggregates displayed a similar distribution pattern (Figure 4).…”
Section: Aggregate-associated Oc Tn and Tp Contentssupporting
confidence: 89%
See 3 more Smart Citations
“…Regardless of the stand type, there were significant differences in OC and TN contents associated with different aggregate sizes, which is shown in Table 2. In this research, OC and TN contents were mainly concentrated in microaggregates (Figure 3), conforming to the results by Mao et al (2021) and Tang and Wang (2022) that microaggregates have larger specific surface areas, causing the adsorption to nutrients to improve. Similarly, our findings detected that soil OC and TN contents with sized aggregates displayed a similar distribution pattern (Figure 4).…”
Section: Aggregate-associated Oc Tn and Tp Contentssupporting
confidence: 89%
“…Irrespective of the stand type, the average OC, TN and TP contents in the bulk soil were 18.95 g kg -1 , 1.10 g kg -1 , and 0.25 g kg -1 , respectively (Table 3), which were lower than the average soil OC (30.40 g kg -1 ), TN (2.21 g kg -1 ) and TP (0.20-1.10 g kg -1 ) contents in China (Tian et al, 2010). N is the common limiting element in C. lanceolata stands of Guangxi (Tang & Wang, 2022;Tong et al, 2020), while China has reached one of the highest N levels reported worldwide, especially in subtropical forests, which have caused increases in soil P loss and decreases in soil P availability (Wang et al, 2018). Soil P sources are relatively fixed (Xue et al, 2022).…”
Section: Aggregate-associated Oc Tn and Tp Contentsmentioning
confidence: 86%
See 2 more Smart Citations
“…Our past research has revealed that the composition and stabilization of soil aggregates change significantly during Chinese fir growth (Tang & Wang, 2022). Nevertheless, the changes of aggregate‐associated bacterial communities in soil over time are still not clear.…”
Section: Introductionmentioning
confidence: 99%